Logaritmos, congruências e estudo sobre radiação solar em Belém e Castanhal - NEVES, Maria Eduarda Noronha das (2024)
This textual production is an academic portfolio, which aims to present the works produced and published during the graduation period, which is not in chronological order in the sections exposed here, as we tried to organize them as indicated in the title of this production. In view of this, four publications produced during 2021 and 2022 are presented, focusing on only three of these productions in the area of applied mathematics and mathematics education. In this way, the Course Completion work, in the portfolio category, reaches the requirement set out in art. 6, paragraph III of Resolution No. 01/2007, in the “publication” mode. The first production is “Teaching logarithmic functions”, presented and published in 2021, with the objective of exposing its historical function and the reasons why mathematics teachers still teach about properties and functions related to the logarithm. In the second academic text, the theme “Congruences and divisibility criteria” is discussed, presented as a poster at the V Symposium on Teaching, Research and Extension, at UFPA, in which the definition and application in the test of nine is introduced. The third academic work corresponds to a data analysis to diagnose the availability of solar radiation in the Castanhal region, taking into account the data corresponding to the years 2011 to 2020, for a total of 10 years. The last publication “Hourly profile of solar radiation in the region of Belém”, aims to present the hourly variation of solar radiation and propose a mathematical model to provide estimated values of received solar energy. Therefore, this portfolio has the proposal to present the productions carried out during the trajectory in the Mathematics Degree course. Furthermore, it should be noted that the academic productions contributed to my personal and academic development, strengthening my goals, fulfilling personal goals and, above all, providing an excellent complement to my professional training.